The neck-tongue syndrome. Issue 3 (March 1994) - Orrell, R W; Marsden, C D
Abstract : The neck-tongue syndrome, consisting of pain in the neck and altered sensation in the ipsilateral half of the tongue aggravated by neck movement, has been attributed to damage to lingual afferent fibres travelling in the hypoglossal nerve to the C2 spinal roots. The lingual afferents in the hypoglossal nerve are thought to be proprioceptive. Two further cases of the neck-tongue syndrome are described, the spectrum of its clinical manifestations is explored, and the phenomenon of lingual pseudoathetosis is illustrated as a result of the presumed lingual deafferentation.